The geochemical and strontium isotope characterisation of South African combustion fly ash and their potential environmental effects - Skhosana, Lungile Charmain (My University, 2023)
The mining of coal in South Africa has played, and continues to play, a vital role in building the country’s economy for over a century and a half. During the combustion of low-grade coal for energy production, a large amount of coal utilisation by-products (CUP), such as bottom ash (BA), coal fly ash (CFA), and flue-gas desulfurization gypsum, are generated. Coal-fired power stations in South Africa produce over 25 Mt of CFA per year, with only ca. 5% being re-utilised for building concrete, agriculture, construction, and backfilling mines. The long-term exposure to weathering of CFA poses pressure on environmental systems. Therefore, a better characterisation of the mineralogy and trace element chemical compositions of CFA, and their potential environmental effects have become increasingly important. Mineralogical and geochemical analyses were carried out on CFA samples sourced from five South African coal-fired power stations: Kriel, Tutuka, Grootvlei, Hendrina, and Komati. The samples were analysed using X-Ray Diffractometry (XRD), X-Ray Fluorescence (XRF) and Inductively Coupled Plasma Mass Spectrometry (ICP-MS). Samples from Tutuka and Kriel Power Stations have been characterised by Strontium (Sr) isotopic analyses. CFA samples of Kriel, Tutuka, Grootvlei, and Hendrina are classified as Class F and alumina-silicate type CFA. The Komati sample is classified as Class N and silico-aluminate type CFA. The trace elements results indicated variability in the toxic elements among the samples with relatively high concentrations of Cr being detected, along with an abundance of transitional metals. These Cr and transitional metal abundances are higher than the Coal Clarke values for CFA determined by Ketris and Yudovich (2009) and thus pose a potential environmental hazard. The Sr isotopic characterisation of bulk CFA has contributed towards using Sr as an environmental tracer for CFA in various parts of the world. However, no such investigation of Sr isotopes as an environmental tracer has been undertaken in South Africa before the current investigation. The results obtained, therefore, form the basis for future studies into the leaching behaviour and mobility of Sr and toxic trace elements. The Sr contents for the five coal-fired power stations range between 810.3 ppm and 1759.0 ppm, ranking higher than the global mean value of ca. 740 ppm (Ketris & Yudovich, 2009) for Sr in CFA. Therefore, the studied CFA may have the potential of being environmentally hazardous; consequently, a leaching procedure would need to be conducted to fully understand the correlation between Sr and the mobility of toxic trace elements. The study into the potential of the Grootvlei, Hendrina, Komati, Tutuka and Kriel CFA as REE sources indicated that the CFA does not qualify as a potential REE source according to the criteria set out by Dai et al. (2017). However, in comparison to REE ore deposits it was discovered that although REY enrichment may be low in the CFA’s, the abundance of CFA far exceeds that of REE ore deposits. Therefore, CFA stockpiles can be considered as potential low-grade disseminated REY mineralisations.